UPDATED GUIDELINE-BASED MANAGEMENT OF HEART FAILURE WITH REDUCED EJECTION FRACTION IN ELDERLY PATIENTS WITH LOW BLOOD PRESSURE - Minh Khánh, Trương; Dương Trung Hào, Âu; Hoàng Phong, Ninh; Ngọc Phương Dung, Nguyễn; Duy Lượng, Đào; Tân, Nguyễn Văn (Journal of Health and Aging, 2025)
Heart failure with reduced ejection fraction (HFrEF) represents a major global health burden, characterized by high rates of morbidity, hospitalization, and mortality, particularly among elderly patients. Low blood pressure is a common condition in this population, associated with worse prognosis and challenges in optimizing guideline-directed medical therapy (GDMT). Evidence from randomized controlled trials and real-world studies demonstrates that the benefits of GDMT persist even in patients with low blood pressure. Among the foundational therapies, sodium–glucose cotransporter-2 inhibitors (SGLT2i) and mineralocorticoid receptor antagonists (MRA) have minimal hemodynamic effects and can be initiated early, whereas angiotensin receptor–neprilysin inhibitors (ARNi), angiotensin-converting enzyme inhibitors (ACEi), and beta-blockers (BB) should be started at low doses and carefully up-titrated. In Vietnam, prescription rates of GDMT remain limited; however, current evidence highlights the importance of maintaining GDMT to the maximum tolerated extent, alongside evaluating secondary causes of hypotension and tailoring therapy to individual patients. This review summarizes updated evidence, discusses pharmacodynamic considerations, and proposes clinical strategies for managing elderly patients with HFrEF and low blood pressure, emphasizing the role of comprehensive geriatric assessment in achieving safe and effective therapy
Keywords: elderly patients; heart failure with reduced ejection fraction; low blood pressure